2008
DOI: 10.1128/aem.02271-07
|View full text |Cite
|
Sign up to set email alerts
|

The BaeSR Two-Component Regulatory System Mediates Resistance to Condensed Tannins in Escherichia coli

Abstract: The gene expression profiles of Escherichia coli strains grown anaerobically with or without Acacia mearnsii (black wattle) extract were compared to identify tannin resistance strategies. The cell envelope stress protein gene spy and the multidrug transporter-encoding operon mdtABCD, both under the control of the BaeSR two-component regulatory system, were significantly up-regulated in the presence of tannins. BaeSR mutants were more tannin sensitive than their wild-type counterparts.Condensed tannins, or proa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
(21 reference statements)
1
35
0
Order By: Relevance
“…The authors used dot-blot quantification to confirm that these Gram-negative bacterial groups predominated in the presence of dietary tannins, and that there was a corresponding decrease in the Gram-positive Clostridium leptum group and in other groups. Mechanisms for Gram-negative higher tolerance to tannins were suggested by Zoetendal et al (2008), which are beyond the scope of this study. In the present study, the Gram-negative isolates could not be identified, but both tolerated up to 2 g L -1 of tannins, and could not ferment cellulose or galactose.…”
Section: Resultsmentioning
confidence: 99%
“…The authors used dot-blot quantification to confirm that these Gram-negative bacterial groups predominated in the presence of dietary tannins, and that there was a corresponding decrease in the Gram-positive Clostridium leptum group and in other groups. Mechanisms for Gram-negative higher tolerance to tannins were suggested by Zoetendal et al (2008), which are beyond the scope of this study. In the present study, the Gram-negative isolates could not be identified, but both tolerated up to 2 g L -1 of tannins, and could not ferment cellulose or galactose.…”
Section: Resultsmentioning
confidence: 99%
“…Tannic acid has long been known to have antibacterial properties (42), bacteria are known to actively modulate gene expression in response to tannins (43,44), and recently, it has been suggested to have antibiofilm properties (45). Pentagalloyl glucose (one of the major components of commercial tannic acid) and ellagic acid (another plant-derived polyphenolic compound) have also been shown to inhibit biofilm formation in S. aureus (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, flavonoids are closely related to condensed tannins, which were previously shown to be more toxic to a strain lacking BaeSR (44). To further test the ability of flavonoids to induce the BaeSR pathway, a number of structurally related compounds were chosen for testing.…”
Section: Sodium Tungstate and Flavonoids Are Novel Inducers Of The Bamentioning
confidence: 99%
“…In one, a phenotypic microarray found that a BaeSR mutant was more sensitive to growth in the presence of sodium tungstate, myricetin, gallic acid, and nickel chloride (43). A more recent study of global gene expression changes in the presence of plant secondary metabolites, called condensed tannins, discovered genes regulated by the Bae pathway to be upregulated in their presence (44). Zoetendal and colleagues also found that BaeSR mutants were more sensitive to growth in the presence of condensed tannins and that overexpression of the MdtABC efflux pump aided in survival under these conditions (44).…”
mentioning
confidence: 99%
See 1 more Smart Citation